Expression of melanoma differentiation–associated gene 5 in the epidermis and cutaneous deposition of complement C3 and immunoglobulins in patients with dermatomyositis - Yoshiaki Zaizen; Takuma Koga; Masahiro Tsutsumi; Shinjiro Kaieda; Jun Akiba; Takekuni Nakama; Tomoaki Hoshino (PLoS ONE, 2026)
Objectives Dermatomyositis (DM) is an autoimmune disease characterized by interface dermatitis, but the immunopathological features underlying cutaneous inflammation remain incompletely understood. The aim of this study was to characterize the cutaneous deposition of complement and immunoglobulins, as well as to clarify the localization of melanoma differentiation-associated gene 5 (MDA5) in DM skin. Methods Skin biopsy specimens from 22 patients with DM and 13 control specimens obtained from cancer-free skin of patients with dermatofibrosarcoma protuberans were examined. Immunohistochemical staining for complement C3c, immunoglobulins (IgG, IgM, and IgA), and MDA5 was semi-quantitatively evaluated, focusing on the superficial dermis near the dermo-epidermal junction. Results Significantly greater deposition of C3c, IgM, and IgA was exhibited by DM skin compared with control skin (all p ≤ 0.001), predominantly localised to the superficial dermis at sites of interface dermatitis. In contrast, IgG showed comparable deposition in both DM and control skin. MDA5 was strongly expressed in the stratum spinosum and basal layer of the epidermis in both DM and control skin. Enhanced MDA5 expression was notably observed in dermal inflammatory cells and capillaries in DM skin, but minimal expression was observed in the dermis of control skin. Conclusions DM skin is characterized by the deposition of immunoglobulins and complement C3c at sites of interface dermatitis, findings that are consistent with immune complex-mediated injury. MDA5 is widely expressed in both DM and control skin epidermis and can be detected in the infiltrating inflammatory cells of DM.